2008
DOI: 10.1682/jrrd.2007.05.0065
|View full text |Cite
|
Sign up to set email alerts
|

Integration of acoustic and electrical hearing

Abstract: Abstract-For some individuals with severe high-frequency hearing loss, hearing aids cannot provide a satisfactory improvement in speech recognition. However, these same patients often have too much residual hearing to qualify as candidates for a cochlear implant. Here we describe results with the Iowa/ Nucleus Hybrid cochlear implant, which is designed to preserve the patient's residual low-frequency hearing while at the same time supplementing their high-frequency hearing through electrical stimulation. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 27 publications
2
58
1
1
Order By: Relevance
“…Though the level of residual hearing may not be sufficient to independently provide meaningful audition (such as speech understanding), it can enhance the auditory capabilities of a cochlear implant user (Turner, Gantz, Vidal, Behrens, & Henry, 2004). Of these two methods of combining acoustic and electric hearing, the use of a conventional aid is the less restricted option, as hybrid devices are implanted only in implant candidates with hearing loss meeting certain criteria: hearing loss of less than 60 dB at 250 Hz, steeply sloping to severe/profound loss by 2000 Hz (Turner, Gantz, & Reiss, 2007). Additionally, placing the HA in the ear contralateral to the CI may provide some of the advantages of binaural hearing, such as sound localization (Ching, Incerti, & Hill, 2004;Ching, Incerti, Hill, & van Wanrooy, 2006) and speech perception in noisy listening environments (Ching et al, 2004;Luntz, Shpak, & Weiss, 2005).…”
mentioning
confidence: 99%
“…Though the level of residual hearing may not be sufficient to independently provide meaningful audition (such as speech understanding), it can enhance the auditory capabilities of a cochlear implant user (Turner, Gantz, Vidal, Behrens, & Henry, 2004). Of these two methods of combining acoustic and electric hearing, the use of a conventional aid is the less restricted option, as hybrid devices are implanted only in implant candidates with hearing loss meeting certain criteria: hearing loss of less than 60 dB at 250 Hz, steeply sloping to severe/profound loss by 2000 Hz (Turner, Gantz, & Reiss, 2007). Additionally, placing the HA in the ear contralateral to the CI may provide some of the advantages of binaural hearing, such as sound localization (Ching, Incerti, & Hill, 2004;Ching, Incerti, Hill, & van Wanrooy, 2006) and speech perception in noisy listening environments (Ching et al, 2004;Luntz, Shpak, & Weiss, 2005).…”
mentioning
confidence: 99%
“…Further clinical trials of the Iowa/Nucleus Hybrid cochlear implant resulted in threshold shifts of 20 dB or less for the majority (70%) of patients (Turner et al, 2008 fibrosis. This approach allowed them to achieve hearing preservation to within 20 dB of preoperative thresholds in 12/14 patients and hearing preservation to within 10 dB of preoperative thresholds in 9/14 patients.…”
Section: Surgical Techniques To Preserve Hearingmentioning
confidence: 99%
“…Since then, clinical results from a large number of studies have indicated improved speech recognition for individuals receiving both electric and acoustic stimulation compared to either electric or acoustic stimulation alone (Gantz et al, 2005;Gantz et al, 2006;Gstoettner et al, 2009;Kiefer et al, 2005;Lorens et al, 2008;Turner et al, 2004;Turner et al, 2008). Although evident for speech in quiet, this benefit provided by EAS is most pronounced for speech in noise.…”
Section: Overview Of Electric-acoustic Stimulation (Eas)mentioning
confidence: 99%
See 1 more Smart Citation
“…With these improved outcomes, cochlear implant (CI) candidacy guidelines for various companies have recently expanded to include individuals with HL in the moderate as well as the severe-to-profound HL range. In addition, advances in electrode design, technology, and surgical techniques have enabled preservation of hearing thresholds in the implanted ear (Gstoettner et al, 2004(Gstoettner et al, , 2006Machado de Carvalho et al, 2013;Mowry, Woodson, & Gantz, 2012;Turner, Gantz, & Reiss, 2008a;Usami et al, 2014).…”
mentioning
confidence: 99%